Perceived Seasonal Impact of Air Pollution on Health and Properties in Port Harcourt - , Susan I. Ajiere; , Bridget E. Diagi; , David Edokpa; , Okorondu J. Nnaemeka; , Ekweogu C. Victoria (Archives of Current Research International, 2022)
Air pollution is an environmental menace that has attracted a lot of concern both locally and globally. The Environment is very important to sustainability of life and air pollution has become of great concern to many countries across the world especially its impact on human health and ecosystem. This study thus, assessed perceived seasonal impact of air pollution on health and property of the inhabitants of Port Harcourt. Primary data in form of questionnaire was used to solicit information from the inhabitants of the study area. A cross-sectional research design was adopted using an online survey and a 24-question survey was designed on goggle documents website (doc.goggle.com). The link was active for three months and was strictly monitored, the link was disabled after receiving 400 responses. Data for the study were analyzed using cross-tabulation and bivariate percentage analysis. Results revealed that majority of the respondents were females (53.2%). However, 73.3% of the respondents have lived in Port Harcourt more than 11 years. This is an indication that they have high knowledge of the environment. Majority of the respondents (79.4%) have observed a change in air quality which was rated low and (80.1%) have attributed the source of the air pollution to illegal refining of crude oil within the city. Fifty percent of respondents identified two Climate seasons: raining and dry and (51.2%) observe the impact of air pollution to be more prominent during the dry season. Majority perceived that the associated health risk is very high (56.5%) and attributed health related issues such as difficulty in breathing, asthma, eye problem, heart problem, increase in cancer and headache to poor air quality in the city. It was also noted that the incidence of sooth affected their properties. Hence, there is an urgent need for government at all levels to put in place adequate enforcement institution that will work with community leaders (youth, women and other), health officials and academic researchers to implement the environmental policies and sanction offenders for the overall benefit of the wellbeing of the inhabitant towards achieving a sustainable environment in the state.